PERANCANGAN SISTEM INFORMASI IN OUT STOCK BERBASIS WEB DENGAN FRAMEWORK CODEIGNITER PADA TOKO METROCHILON PAPUANA GEMILANG (MPG) WOSI : PERANCANGAN SISTEM INFORMASI IN OUT STOCK BERBASIS WEB DENGAN FRAMEWORK CODEIGNITER PADA TOKO METROCHILON PAPUANA GEMILANG (MPG) WOSI - Pramana Aschary, Dhian; Suhendra, Christian Dwi; Pangaribuan, Bertha (Universitas Papua, 2024)
With the aim of overcoming management and storage problems that still use manual methods in storing data, products, incoming goods, and outgoing goods along with each existing report. It is felt to be less effective and inefficient, because if there is an addition to product data, incoming goods, outgoing goods along with each data report must be studied in detail as a whole, so as to provide ineffectiveness in data processing and storage. The impact of this problem is the delay in providing reports to business owners. and with the existence of an application system